A framework for regulating microfinance institutions : the experience in Ghana and the Philippines - Gallardo, Joselito S., 1938- 1938- (Policy research working paper, 2002)
How does a country's legal and regulatory framework affect the sustainability of microfinance? Does a tiered approach to regulation help to integrate microfinance into the formal financial system? And are there lessons to be learned from the experience of Ghana and the Philippines with a tiered approach?